The Role of Customer Engagement in Mediating the Influence of Brand Experience and Customer Satisfaction on the Customer Loyalty of Full-Service Airline in Indonesia - Roffianto Adi Nugroho; Ni Wayan Sri Suprapti (Profesional Muda Cendekia Publishing, 2022)
The Corona Virus Disease-19 (COVID-19) pandemic, which is currently engulfing the entire world, has significantly reduced the number of air travel passengers worldwide. However, the decline in air travel passengers on domestic routes in Indonesia occurred in 2019, one year before the COVID-19 pandemic hit the aviation industry worldwide. The decline in passengers in 2019 can be taken as a signal of weakening demand in the aviation industry in Indonesia. This research was conducted on 233 respondents from the airline